POUPATEMPO: um programa de atendimento ao cidadão - Painelli, Sérgio (2008)
The political, economic and social changes resulting from ideological changes, globalization, search for competitiveness, among others, have brought many challenges to companies and the national States. The private sector sought immediately, in this context, new methods of management as a way to increase productivity, reduce costs, and optimize the invested capital, to value the efficiency, effectiveness and quality to ensure competitive advantage in a market of increasingly fierce competition. In the same way, the State was mobilized and the answer was found through administrative modernization, more specifically, through the management reform, whose focus on results imply, among other aspects, in strengthening the citizenship concept, strengthening values such as efficiency and effectiveness and also managing with focus on the citizen, searching to improve the quality of services. The implementation of a management model in this pattern, implies in modifying a rooted culture associated to a bureaucratic management. It involves a change in beliefs, values and attitudes of employees and organization as a whole. Therefore, this study seeks to analyze the implementation of the program currently called Poupatempo Central de Atendimento ao Cidadão, which lasts already for ten years and that made it possible to provide quality services to the population. The results demonstrate the innovative character of the Programa Poupatempo and from the user s research for satisfaction it was possible to evidence that, in general, they are very satisfied in relation to the services and that it is possible to achieve excellent levels in providing these services in public administration since that associated with cultural changes